Adaptation and Innovation of Pesantren in Facing the Challenges of the Global Millennial Era - Nurdi; Nashrulloh; Rohim Habibi (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
Islamic boarding schools (pesantren) currently face dual challenges: maintaining traditional orthodoxy while responding to global technological disruption. This study aims to analyze resilience and adaptation strategies used by pesantren to bridge the values of student (santri) obedience with the characteristics of a critical digital generation. Employing a qualitative approach with a library research method, the data were analyzed descriptively to examine contemporary challenges within the Islamic education ecosystem. The results indicate that pesantren adaptation is manifested in four strategic domains: (1) Curriculum reconstruction through the integration of classical Islamic texts (turats) with scientific-technological literacy; (2) Strengthening digital literacy as a filter against radicalism and hoaxes; (3) Mainstreaming religious moderation (wasathiyyah) as a counter-narrative to extremism; and (4) Fostering economic independence based on sociopreneurship. This article concludes that the sustainability of pesantren depends on its ability to recontextualize values through the principle of al-muhafadhah ‘ala al-qadim al-shalih wa al-akhdzu bi al-jadid al-ashlah (preserving good old traditions while adopting better new ones). Supported by Law No. 18 of 2019, pesantren have the potential to transform into centers of Islamic civilization that are authentic yet globally relevant.